PHYSICAL, MECHANICAL, AND MORPHOLOGICAL CHARCTERISTICS OF KAPOK (CEIBA PENTANDRA) TREE BARK AND EPOXY COMPOSITE WITH COATING (AESO) TREATMENT - Suparjon Suparjon; Femiana Gapsari; Budi Purnomo (Jurnal Rekayasa Mesin, 2023)
Environmentally friendly composites continue to be developed from kapok tree fiber (Ceiba pentandra) with an epoxy matrix. This study aims to characterize the tensile behavior of single fiber and its composite, the pull-out properties of kapok tree fiber, and morphology of the fiber. Kapok tree fibers were varied in the NaOH solution and the AESO polymer. Single fiber tensile test and pull out refer to the ASTM D3379-75 and ASTM E399 standards, respectively. The composite manufacturing method used in this research was the infusion vacuum resin method with reference to the ASTM D638 standard. The results of the tensile test (composite) showed that the kapok bark fiber with the characteristics of NaOH + Coating had a greater tensile strength (197,88 Mpa), than that without treatment and NaOH treatment. Of all the characteristics of the kapok bark fiber, the highest value of the tensile strength was the fiber treated with NaOH + Coating (KNC). The results of fiber morphology showed proved that the NaOH treatment increased the surface hardness by eliminating the bonds of surface crystallinity, topography, water absorption, unit cell structure and fiber orientation. These results indicate that kapok tree fiber treated with 7% NaOH + coating with AESO polymer has high potential as a structural material to replace wood or textile materials.